Socioeconomic Inequalities in Pregnancy Termination among Young Women in Cambodia: A Cross-sectional Analysis of the 2021–22 Demographic and Health Survey - Sokha, Yem; Sokunthea, Kem; Lida, Vann; Sreypeov, Tun (Asian Journal of Public Health and Nursing, 2026)
Background: Pregnancy termination among adolescents and young women reflects gaps in contraceptive access, unmet need for family planning, and unequal access to sexual and reproductive health information and services. In Cambodia, limited recent national evidence exists on socioeconomic patterns and determinants of pregnancy termination among young women, despite persistent adolescent fertility and early marriage. This study aimed to estimate the prevalence of pregnancy termination among adolescents and young women in Cambodia and examine socioeconomic patterns and associated factors using data from the Cambodia Demographic and Health Survey (CDHS) 2021–22. Methods: This cross-sectional secondary analysis used nationally representative data from the CDHS 2021–22 women's questionnaire. The study population included women aged 15–24 years (N=5,783). The outcome was a self-reported history of pregnancy termination, based on DHS standard definitions. Key exposures included wealth index, education level, and place of residence. Additional covariates included age group, marital status, parity, employment status, media exposure, and contraceptive use. Survey-weighted descriptive statistics and multivariable logistic regression were used to examine associations while accounting for complex survey design. Results: The overall prevalence of pregnancy termination was 5.28% (95% CI: 4.52–6.16). Prevalence varied significantly by socioeconomic status: 3.8% among women from poor households, 5.3% among middle-income, and 6.8% among wealthy households (p<0.001). Women with secondary or higher education had higher prevalence (6.2%) compared to those with no education (3.9%, p<0.001). In multivariable analysis, factors significantly associated with increased odds of pregnancy termination included wealthier households (aOR=1.82, 95% CI: 1.24–2.67), higher education (aOR=1.58, 95% CI: 1.09–2.29), urban residence (aOR=1.44, 95% CI: 1.08–1.92), older age 20–24 years (aOR=2.15, 95% CI: 1.61–2.88), union status (aOR=3.42, 95% CI: 2.48–4.71), and women with two or more children (aOR=5.68, 95% CI: 3.92–8.23). Conclusion: Pregnancy termination among young Cambodian women shows a distinct positive socioeconomic gradient, with higher prevalence among wealthier and more educated women, contrasting with patterns in some high-income countries. The strong association with parity indicates that termination is primarily used for birth spacing and limiting. These findings highlight the need for strengthening youth-focused sexual and reproductive health services and ensuring equitable access to quality contraception across all socioeconomic groups.